Performance Studies Floating Free of Theatre. Richard Schechner and the Rise of an Open Interdisciplinary Field - Deriu, Fabrizio (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2013)
As Marvin Carlson points out, the term performance has recently developed “as a central metaphor and critical tool for a bewildering variety of studies, covering almost every aspect of human activity.” While there is a tendency to stress their similarities and theoretical convergence, Performance Studies and Cultural Studies have different origins: the roots of Performance Studies are clearly located in theatre studies and practices. The essay outlines a short history of the rise of Performance Studies, focussing on Richard Schechner’s work. According to him, a Performance Studies paradigm came to the fore in the mid-1950s, with books by Bateson, Austin, Goffman, Caillois and others. In the Sixties Schechner started to teach and was founder/director for influential theatre groups on the American avant-garde scene. When his interest shifted from theatre to performance and from aesthetics to social sciences, he found anthropology extremely useful because in ethnographies anthropologists treat the actual lived behaviours of people performatively. Schechner developed these assumptions and cooperated intensely with social scientists, in particular the anthropologist Victor Turner. In 1980 Schechner co-founded the Department of Performance Studies at NYU. Since then many academic institutions have started similar programs; Schechner’s books have been translated into many languages; and worldwide a growing cohort of scholars have been attracted to this stimulating, inter-disciplinary, threshold-crossing approach.